Character Building: Internalization of Religious Values in Institutions Children's Special Coaching - Nur Hamzah; Ratna Pangastuti; Bayu Suratman; Rahnang Rahnang (AT-TURATS, 2022)
This article is based on the results of research conducted at a special child development institution in Pontianak. The focus of this paper is the internalization of religious values carried out on students at the Pontianak Special Child Development Institute. The purpose of this study is to find the cultivation of religious values in a special child development institution in Pontianak. The results of this study show that the internalization of religious values is carried out in several religious activities such as: congregational dzuhur prayers, Friday prayers, dhuha prayers, Saturday recitations, joint recitations, recitations in the month of Ramadan, and Islamic holidays. The activity aims to generate individual and social piety of students. Piety that students have as capital to gain re-admission in the community for criminal acts that have been committed. Individual and social piety is a religious habitus instilled in students through cognitive, affective, and psychomotor aspects to rationally make students aware of the social capital that will be received by society when they leave the special child development institution in Pontianak. This writing is a qualitative descriptive research where data is obtained based on the results of interviews, observations, and documentation at the research site.